(2E)-N′-[(E)-2-Hydroxybenzylidene]-3-phenylprop-2-enohydrazide - Carvalho, Samir A. (International Union of Crystallography, 2012)
In the non-planar title compound, C(16)H(14)N(2)O(2), the dihedral angle between the phenyl rings is 16.67 (8)°. An E conformation is found for each of the imine [1.286 (2) Å] and ethylene [1.335 (2) Å] bonds. The amide O and H atoms are anti, and an intramolecular hydroxy O—H⋯N hydrogen bond is noted. The formation of N—H⋯O(hydroxy) hydrogen bonds in the crystal packing leads to helical chains along the b axis. Supramolecular layers in the ab plane are formed as the chains are linked by C—H⋯O interactions.